Sudden, unexpected and natural death in young adults of age between 18 and 35 years: A clinicopathological study - Madhu Chaturvedi; Meera Satoskar; Manisha S Khare; Alka D Kalgutkar (Wolters Kluwer Medknow Publications, 2011)
Context: To identify various causes, risk factors, age and sex distribution associated with sudden and unexpected natural deaths (SUNDs) in young adults of age between 18 and 35 years. Materials and Methods: Retrospective analysis of autopsy reports and medical records of all SUNDs that occurred instantaneously or within 24 hours of onset of symptoms in young adults, between 2001 and 2009. Result: Of the total 6453 deaths autopsied during 2001-2009, 64 (0.99%) were SUNDs in young adults, chiefly in males between 30 and 35 years of age. Non-cardiac causes significantly predominated (73.4%) over cardiac causes (7.8%). Most of the SUND cases were due to preventable causes, including infections (54.6% cases), cerebrovascular accidents (9.37%) and ischemic cardiac causes (6.25%). Sudden adult death syndrome (SADS) accounted for 18.75% deaths. Conclusion: SUND in young adults is preventable. A meticulous post-mortem examination with special attention to the conduction system of heart and detailed toxicological analysis can pinpoint the cause of death in SADS.